2015
DOI: 10.1177/1352458515593406
|View full text |Cite
|
Sign up to set email alerts
|

Radiological differentiation of optic neuritis with myelin oligodendrocyte glycoprotein antibodies, aquaporin-4 antibodies, and multiple sclerosis

Abstract: MOG-ON and AQP4-ON are more commonly bilateral and longitudinally extensive. MOG-ON tends to involve the anterior optic pathway, whereas AQP4-ON the posterior optic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
282
9
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 317 publications
(319 citation statements)
references
References 32 publications
17
282
9
11
Order By: Relevance
“…Furthermore, 4.9% of children with MOG-ON had an optic chiasm lesion, indicating the MRI manifestation of MOG-ON can be longitudinally extensive. No differences were found in the MRI features of the AQP4-ON and MOG-ON groups, which is in contrast to the study by Ramanathan et al ,33 where MRI lesions in patients with MOG-ON tended to involve the anterior optic nerve segment and AQP4-ON lesions were in the posterior optic nerve segment.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, 4.9% of children with MOG-ON had an optic chiasm lesion, indicating the MRI manifestation of MOG-ON can be longitudinally extensive. No differences were found in the MRI features of the AQP4-ON and MOG-ON groups, which is in contrast to the study by Ramanathan et al ,33 where MRI lesions in patients with MOG-ON tended to involve the anterior optic nerve segment and AQP4-ON lesions were in the posterior optic nerve segment.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding was consistent with previous reports that compared between MOG-ON (32.29±17.1 years old) and AQP4-ON (44.86±14.8 years old),8 MOG-ON (31 years old) and AQP4-ON (38 years old),10 MOG-ON (20±14 years old) and AQP4-ON (23±14 years old) 26. More than half (65%) of our patients with MOG-ON had a juvenile (<18 years) disease onset, which was more than those reported by previous study showing about 12.5%,9 50%10 or 16.7%13 of MOG-Ab-positive patients with demyelinating diseases began during juvenile period.…”
Section: Discussionsupporting
confidence: 93%
“…Bilateral ON and optic disc swelling were commonly observed in our Chinese MOG-ON cohort, which was corresponding with those patients with MOG-ON in various ethnic groups 26. However, previous reports indicated that most of the MOG-Ab-positive patients presented as monophasic disease or had less relapsing rate,8 9 which was different from the current study demonstrating both patients with MOG-ON and AQP4-ON had high recurrent episodes.…”
Section: Discussioncontrasting
confidence: 82%
“…1,2 There have only been 2 cases reported of large hemispheric or tumefactive lesions. 1,4 Our patient had a less common presentation with symptomatic large hemispheric tumefactive lesions, concurrent with the third episode of LETM, which is a core clinical characteristic for NMOSD. 3 Histopathology of active lesions from AQP4-seropositive patients with NMO showed inflammatory infiltrate with reduction or loss of GFAP-positive astrocytes, or astrocyte cytologic abnormalities.…”
mentioning
confidence: 89%